Customers’ Satisfaction Toward Service Quality of Hub Property Service Company Limited - วรพต, มะลิวัลย์; วงษ์เล็ก, ภูษิตย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed 1) To study the customers’ satisfaction toward service quality of Hub Property Service Company Limited. And 2) To compare the customers’ satisfaction toward service quality of Hub Property Service Company Limited, the population consists of service users of Hub Property Service Co., Ltd. in the year 2024, totaling 350 people. The sample group comprises 305 people, derived through the purposive sampling. The instruments used for the research were the questionnaire with the content validity (IOC) of 0.67 - 1.00 and the reliability of the questionnaire 0.95. The statistics which were used in the data analysis were percentage, mean and standard deviation. The hypothesis testing analyzed by t-test and One-way ANOVA (F-test) for testing of variance as well as pair-wise comparison by means of Scheffe’s method which were conducted at the statistical significance level of 0.05.The results of the research revealed that: 1) The customers were satisfied toward the service quality of Hub Property Service Company Limited, overall and all aspects were at a high level. The highest satisfaction was the empathy; the subordinate satisfactions were the tangibles, the responsiveness, the assurance, and the reliability. 2) The customers who were different age, level of education, occupation, and income per month satisfied toward service quality of Hub Property Service Company Limited, overall, showed the difference at the statistical significance level of 0.05 but the customers who were different gender satisfied toward service quality of Hub Property Service Company Limited, overall, showed no difference.